Analisis Disparitas Penjatuhan Sanksi Pidana Terhadap Anak Sebagai Pelaku Tindak Pidana Penganiayaan (Studi Kasus Putusan Pengadilan Negeri Pekanbaru dengan No Perkara 14/Pid.Sus-Anak/2019/PN Pbr dan No Perkara 22/Pid.Sus-Anak/2019/PN Pbr ) - ALBERT PH SILALAHI; Mukhlis R; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
In the same case, law has different rules. In law, it is known as disparity (disparity of sentencing). According to Oemar Seno Adji, disparity does what can be justified as long as it is done naturally. In writing this thesis the author discusses the problem of Criminal Disparity in cases of Criminal Abuse committed by children in case No Case 14 / Pid.Sus-Anak / 2019 / PN Pbr with Case No Case 22 / Pid.Sus-Anak / 2019 / PN Pbr. For the purpose of writing this thesis, namely; First, we can find out the causes of the disparity in crimes committed by judges in deciding criminal acts of maltreatment committed by children. Second, we can find out the ideal sanctions given by judges to child defendants.The research method used is the normative juridical method in relation to Restoratif justice. The results show that in deciding a case the judge is subject to Article 197 of the Criminal Procedure Code, namely the judge must have his own consideration in determining the severity or lightness of the sentence to be imposed on the defendant, through material evidence in court to support the conclusions in the judge's consideration.The result of this study is that in deciding a case, a judge pays attention to matters or methods properly and fairly without any political interests or personal interests that can harm one of the parties. In the case of a criminal act of torture committed by Anak Bintang Nusantara Als Bintang Bin Ali Basyah, et al, they are subject to Article 170 Paragraph (2) Section 2e of the Criminal Code Jo Article 20 of Law no. 11 of 2012 by Judge ABDUL AZIZ, SH, M.HUM with 5 years in prison, and against the defendant Anak Agusfah Yani Als Yani Binti Herman and Anak II Rama Dani Als Rini Binti Herman, Judge Dahlia Panjaitan SH Wearing Article 80 of the Criminal Code paragraph 1 KUHP in conjunction with Article 76 c of Law No. 35 of 2014 with 3 months in prison without considering Restorative justice for the child of the Defendant.Keywords: Disparities-Court Decisions-Judge-Restorative Judgments